Solar PV- and PEM electrolyzer-based green hydrogen production cost for a selected location in Bangladesh - Gour Chand Mazumder; Sakibul Hasan; Md. Saniat Rahman Zishan; Md. Habibur Rahman (Academia Green Energy)
Hydrogen is considered to be the environmentally safest energy source. Green hydrogen has no carbon footprint as it is produced from renewable energy sources. The barrier is the high production cost of hydrogen for all through usage of it. The use of solar photovoltaic (PV) electricity for polymer electrolytic membrane-based electrolysis may lower the production costs. Estimation of hydrogen production cost is performed using the life cycle cost (LCC) method. The PV electricity cost was calculated using the HOMER Energy Software. Lifetime of the project is 25 years with a 7.48% discount rate. The electricity cost is about Bangladeshi Taka (BDT) 39.91/kWh from solar PV. The system consumes 6,011 kWh of electricity and produces 42.44 kg of hydrogen per year. The LCC result shows that the hydrogen production cost is about BDT 230.90/g. Bangladesh might consider giving emphasis for green hydrogen production and help establish a green hydrogen economy.